Pertumbuhan Bawang Merah (Allium ascalonicum L.) Varietas Bima Brebes dengan Tujuh Macam Komposisi Blotong Tebu dan Pupuk Kandang Sapi - Gustiar, Fitra; Sodikin, Erizal; Nanda Hasibuan, Aulia; Alkhair, M. Hafiz; Agustin, Aliya; Angreini, Erina; Pratiwi, Maiyola; Reli, Rapita (Seminar Nasional Lahan Suboptimal, 2023)
Gustiar, F., Sodikin, E., Hasibuan, A.N., Alkhair, M.H., Agustin, A., Angreini, E., Pratiwi, M., & Reli, R. (2023). Growth shallots (Allium ascalonicum L.) Variety bima brebes with seven composisitions of sugarcane blotong and cow manure. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang 21 Oktober 2023. (pp. 214-222). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Bima brebes shallot variety is shallot variety that is widely cultivated by farmers because it is easy to grow, in recent years farmers have experienced a 50% decrease in yield due to decreased soil frtility due to chemical fertilisers, to overcome this the use of chayote blotong and cow manure can be used for shallots, this study aimed to determine the growth of shallots (Allium ascalonicum L.) bima brebes varieties with seven different compositions of sugar cane blotong and cow manure. The method used was the research method of Randomized Group Design (RGD) consisting of 7 treatments, with the composition (soil: sugar cane blotong: manure) namely P0 (2:0:0), P1 (2:2:0), F (2:2.5:0.5), P3 (2:1:1), P4 (2:0.5:1.5), p5 (2:0:2), and P6 (1:1:1) analysed by variance analysis (ANOVA). The results of applying mixed manure had an effect on shallot plant height, number of leaves, fresh weight and dry weight of stalks, fresh weight of beetles, dry weight of beetles, number of bulbs, diameter of bulbs and measurement of root length, but had no significant effect on the number of seeds and greenness of leaves. Mixture of soil: sugarcane blotong: cow manure with P2 (2:1.5:0.5) was the best treatment and P5 (2:0:2) was the slowest treatment. The conclusion of this study shows that the combination of sugarcane blotong and cow manure on shallots can increase growth and production. It is recommended that further research be carried out in the field in order to obtain a more appropriate dose of shallots.